Miliary tuberculosis and acute respiratory distress syndrome - Boushab Mohamed Boushab; Leonardo Kishi Basco (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2019)
Background: Miliary tuberculosis is a serious and uncommon form of tuberculosis due to hematogenous dissemination of Mycobacterium tuberculosis. Objective: This study aimed to describe the epidemiological and clinical features of miliary tuberculosis. Patients and Methods: Data were collected from clinical files between August 2016 and July 2018. Results: In 2 years, 24 cases were recorded, representing a proportional morbidity of 13%. Among them, 71% were smokers and 38% had diabetes. The presence of a BCG vaccination scar was observed in 2 patients (8%). Human immunodeficiency virus (HIV) serology was positive in 4 cases (17%). The symptomatology was dominated by: fever (100%), cough (83%), and chest pain (79%). Radiological images with micronodular opacities were the most common (54%), followed by macronodular densities (33%), and reticulonodular densities (13%). The evolution was favorable in 77%, with no patient lost to follow-up, but 7/24 (29%) died, either before the initiation of therapy (n = 2) or during therapy (n = 5). Conclusion: Miliary tuberculosis is an acute and severe form of life-threatening tuberculosis. It requires a prompt and accurate diagnosis and treatment. An improved accessibility to early diagnosis and treatment and prevention of TB infection should reduce its prevalence. Keywords: Diagnosis, Miliary tuberculosis, Mauritania